Valuing carbon stocks across a tropical lagoon after accounting for black and inorganic carbon: bulk density proxies for monitoring - John Barry Gallagher; Swee, Theng Chew; John Madin; Anitra Thorhaug (Coastal Education and Research Foundation, Inc., 2020)
Total organic carbon (TOC) stocks of seagrass and mangroves across a Southeast Asian lagoon were measured and valued after correcting for black carbon (BC) and calcareous carbon equivalents (PICequiv) in mitigating CO2 emissions, along with sediment dry bulk densities (DBDs), as a cost-effective means of estimating carbon stock concepts. Overall, seagrass and mangrove TOC densities ranged from 15.3 ± 4.3 and 124.3 ± 21.1 Mg C ha–1, respectively, across the lower lagoon and 175.2 ± 46.9 and 103.2 ± 19.0 Mg C ha–1 for seagrass and 355.0 ± 24.8 and 350.3 ± 35.2 Mg C ha–1 for mangroves across the two upper lagoon branches. Only mangrove biomass made significant additional contributions, ranging from 178.5 ± 62.3 to 120.7 ± 94.8 Mg C ha–1 for lower and upper regions, respectively. The difference between the lagoon's seagrass and mangrove TOC total stock (5.98 ± 0.69 and 390 ± 33.22 Gg C, respectively) was further amplified by the larger mangrove area. When corrected for BC and PICequiv, the carbon stock mitigation service was reduced by a moderate 14.2%. Across the lagoon the sedimentary DBD showed strong (R2 = 0.85, p < 0.001) to moderate (R2 = 0.67, p < 0.001) linear correlations with seagrass and mangrove [TOC], respectively and moderate correlations with seagrass [PIC] (R2 = 0.6, p < 0.001). There was an invariant and relatively constant response to mangrove [PIC] (2.7 ± 0.07 kg m–3). Valuations were worth on average US$0.44 million y–1 over 20 years, and less than the total income of the indigenous custodians (US$1.8 and US$7.4 million y–1).